The Impact of Banks' Balance Sheet and Profit and Loss Items on Their Financial Performance in the Foreign Exchange Revaluation Process - Kiarostami, Bahareh; Rahmani, Ali (Business, Marketing, and Finance Open, 2025)
The central bank, as the banking regulatory authority, plays a major role in formulating banking regulations, determining the principles of banking operations, setting exchange rates, and other related matters. The Audit Organization, in accordance with its statute, is responsible for developing accounting and auditing standards. The Tax Affairs Organization is also the legal entity responsible for tax assessment and collection from banks. In recent years, conflicts between accounting standards, tax regulations, and the requirements set by the central bank have created numerous challenges for banks. The present study aims to examine the impact of banks' balance sheet and profit and loss items on their financial performance in the foreign exchange revaluation process. The research population includes all banks listed on the Tehran Stock Exchange that have been continuously active from 2014 to 2023. The study sample consists of the following banks: Shahr, Karafarin, Tourism, Eghtesad Novin, Saman, Sarmayeh, Ayandeh, Saderat, Mellat, Parsian, Pasargad, Post Bank, Tejarat, Middle East, Dey, and Sina. The collected data were processed in EXCEL and analyzed using EVIWES12 software. The results indicate that effective management of foreign exchange risks and close monitoring of banks' foreign exchange positions can contribute to improving financial performance and mitigating the adverse effects of exchange rate fluctuations. The findings further reveal that changes in the net open foreign exchange position, particularly foreign exchange revaluation gains or losses, can have a direct impact on return on assets. An increase in foreign exchange revaluation gains enhances return on assets, whereas foreign exchange revaluation losses lead to a decline in this return.